Effective Behaviors in Work Teams: Spanish Adaptation of the Individual Behavior Analysis Scale - Bonavia, Tomas; Julián, Martín (Frontiers in Psychology, 2022)
There are hardly any instruments to measure teamwork behaviors from an individual approach. This applies both in interprofessional teams or not, and in teams involved in health, social care, and other areas. The Individual Behavior Analysis (IBA) scale measures efficacious behavior in work teams. It is one of the few instruments proposed in the literature to measure personal skills necessary for teamwork. Only a previous exploratory analysis of the scale was informed in another study. This article analyzes its internal structure using different confirmatory factor analyses and its internal consistency, with a sample of 815 employees working for Spanish social organizations in the geriatric field, both private and public. The results of the definitive version adapted to Spanish, referred to as IBA-25, indicate a good fit of the model to the data and good reliability. Factor analysis confirmed the existence of two factors: Communication skills and Acceptance, with good internal consistency coefficients. The IBA-25 scale is a useful instrument for assessing, based on the reviewed literature, two of the most important individual skills an efficacious team should have.